Ethnobotanical Survey and Antioxidant Properties of Plants Used Locally in the Management of Cancer in Fika and Fune Local Government Area of Yobe State - U.M Jajere; G. Ibrahim; M.S Abubakar; M.G. Magaji; M. Bashir (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The uncontrolled traits of growth, invasion and sometime metastasis displayed by group of cells is a class of disease called Cancer. Ethnobotanical survey was employed to collect data from the prominent and selected traditional medicinal practitioners and the instrument used was questionnaire to collect data. In vitro Antioxidant activities of the surveyed plant’s extracts were measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH). A total of 30 healers from Fika and Fune LGA of Yobe State- Nigeria were involved in the study. Fouty six (46) plants species were identified and their information with respect to cancer were documented. Antioxidant assay revealed better inhibitory concentration (IC50) and percentage inhibition (%INH) effects at minimum concentration by Boswellia dalzielli, Dichrostaschy cineria and Vitellaria paradoxa with percentage inhibitions and inhibitory concentration (IC50) of 58% (1.16), 58% (1.19), and 58% (1.19) respectively in comparison with standard drug (Ascorbic acid) with percentage inhibition and inhibitory concentration (IC50) of 45% (1.2). Thus, it could be concluded that all the plants collected in this study shows antioxidant potentials which could be attributed to the presence of chemical compounds in the plants, additionally, it can prove its uses in management of cancer traditionally.